Development Potential of Integrated Farming System (Local Cattle - Food Crops) - Elly, Femi Hadidjah; Lomboan, Agustinus; Kaunang, Charles L.; Rundengan, Meiske; Poli, Zulkifli; Syarifuddin, Syarifuddin (ANIMAL PRODUCTION, 2019)
Local cattle farming as an income source for farmers in rural areas is mostly developed traditionally. The local cattle farm continues, even though it is a side business, but is a mainstay in supporting national beef needs. The problem is whether integration of local cattle and food crops have the potential to be developed by farmers. The research was conducted to determine the potential integration of local cattle local and corn in North Bolaang Mongondow Regency. A survey method using a purposive sampling selected 60 farmers from Sangkub District where farmers practiced an integrated cattle-crops farming. Data were subjected to proximate and feasibility analysis. The results showed that the total cattle owned by respondents were 209. The feed consisted of grass and corn waste, with an average consumption of 5.33 and 11.15 kg/head/day, respectively. A proximate analysis of waste corn reported 86.48% dry material, 7.36% crude protein, 1.84% fat, 28.95% crude fiber, 9.10% ash and 68.18% carbohydrate.Â  Respondents' income from cattle farming in Bintauna and Sangkub Districts were Rp. 151,000,000 vs. Rp. 169,900,000, production costs were Rp. 101,150,625 vs. Rp. 107,298,593.8, and RC ratio was 1.49 vs. 1.58. In conclusion, corn waste consumption was greater (67.66%) than the grass. RC ratio value >1 indicated that cattle farming was feasible. The corn-cattle farming integration system can minimize environmental pollution because it enables the concept of LEISA (Low External Input Sustainability Agriculture).